Excessive Se on RuSe2 nanocrystals to accelerate water dissociation for the enhanced electrocatalytic hydrogen evolution reaction. Issue 46 (24th November 2020) - Wang, Kefeng; Li, Bin; Wei, Wei; Wang, Jingge; Shen, Qi; Qu, Peng
Abstract : Excessive Se on RuSe2 nanocrystal surfaces would lower the water dissociation energy barrier, leading to an accelerated HER process. Abstract : Selenium-enriched RuSe2 (Ru x Se) nanocrystals as electrocatalysts for the HER in basic media have been synthesized via a facile hydrothermal method followed by a calcination process. The catalytic activity of the obtained Ru x Se nanocrystals is greatly dependent on calcination temperatures. The nanocrystals obtained at 400 °C (Ru x Se-400) demonstrate the highest HER activity with a low overpotential of 45 mV to deliver a current density of 10 mA cm −2 and a small Tafel slope of 31.4 mV dec −1 . The enhanced catalytic HER performance of Ru x Se-400 could be attributed to the excessive Se on the RuSe2 nanocrystal surface. Density functional theory (DFT) calculations reveal that the excessive Se would lower the energy barrier for water dissociation and lessen the dependence on the Ru sites for OH* adsorption but have a negligible effect on hydrogen adsorption energy, leading to an accelerated HER process. Furthermore, the excessive Se on the nanocrystal surface further endows the catalyst with promoted charge-transfer kinetics, ensuring a more efficient catalytic reaction. The strategy herein for the design of highly efficient HER catalysts by engineering the separation of different intermediate (H* and OH*) adsorption sites is expected to be extended to other electrocatalysts for high-efficiency energy conversion.